A critical review of Pongamia pinnata multiple applications: From land remediation and carbon sequestration to socioeconomic benefits. (15th December 2022) - Degani, Erika; Prasad, M.V.R.; Paradkar, Anant; Pena, Rodica; Soltangheisi, Amin; Ullah, Ihsan; Warr, Benjamin; Tibbett, Mark
Abstract: Pongamia pinnata (L.) Pierre (Pongamia) is a tree native to Southeast Asia. Recently, interest in Pongamia focused on its potential as a biofuel source as its seeds contain around 40% oil. However, Pongamia has multiple applications beyond biofuel production. It is a legume, can form symbiotic associations with mycorrhizal fungi, has been shown to be tolerant to drought, salinity, and heavy metals in soil, and has potential to mitigate climate change. Additionally, Pongamia oil has medicinal properties, can be used as biopesticide, insect repellent, to produce soap, and as a source of edible grade vegetable oil. The seed cake can be used as a source of bioenergy, food and feed protein, and organic fertiliser, and the flowers are a good source of pollen and nectar. Pongamia can also bring socio-economic benefits as its ability to restore degraded and contaminated land provides opportunities for local communities through novel valorisation pathways. These multiple applications have potential to form part of a circular bioeconomy in line with sustainable development goals. Although research on the multiple applications of Pongamia has grown considerably, knowledge gaps remain and these need to be addressed so that the full potential of Pongamia can be achieved. Further understanding of the mechanisms underlying its resilience to abiotic stresses, phytoremediation potential and biotic interactions should be a priority, and co-ordinated breeding efforts will be key. Here, we critically review the available literature on Pongamia and highlight gaps in knowledge in which future research should focus on to ensure that the full potential of this versatile tree can be achieved. We conclude that Pongamia can potentially form part of a circular bioeconomy and that harnessing the multiple applications of Pongamia in a holistic manner, with collaboration among key stakeholders, is crucial for the successful application of its benefits far beyond biofuel production. Graphical abstract: Image 1 Highlights: Pongamia pinnata has multiple applications beyond biofuel production. It has varying levels of tolerance to drought, salinity, and heavy metals in soils. It has potential to mitigate climate change through CO2 sequestration. By restoring degraded land, it can bring socio-economic benefits to communities. It can be part of a circular bioeconomy in line with sustainable development goals.